Image-enhanced endoscopy improves visibility of endoscopic images in individuals with color vision deficiency - Ohno, Akiko; Miyoshi, Jun; Kusuhara, Mitsunori; Jinbo, Yoko; Kaji, Ryosuke; Shirakawa, Takahiro; Watanabe, Moegi; Tsubata, Shiori; Sumi, Ryutaro; Matsuura, Minoru; Iga, Koichi; Okabe, Masataka; Hisamatsu, Tadakazu (Endoscopy International Open, 2025)
Color vision deficiency (CVD) may affect perception of color information in gastrointestinal endoscopy. However, the color-universal concept in endoscopy remains underappreciated. We hypothesized that image-enhanced endoscopy (IEE) could improve object/lesion visibility regardless of CVD and tested this hypothesis with volunteers of varying color vision characteristics.Sixty objects/lesions (20 each of submucosal vessels during colorectal endoscopic submucosal dissection, superficial esophageal cancer, and early gastric cancer) were evaluated. Images with WLI and IEE (red dichromatic imaging [RDI], narrow-band imaging [NBI], or indigo carmine) were assessed for each object/lesion. Twenty evaluators (9 with general color vision: Type C and 11 with two types of CVD [7 with protanopia: Type P and 4 with deuteranopia: Type D]) scored vessel and lesion visibility using a four-level scale.RDI significantly improved the visibility of submucosal vessels in Types P and D (P < 0.0001) compared with WLI, but not in Type C. NBI significantly improved visibility of superficial esophageal cancer compared with WLI in all color vision types (P < 0.0001). Indigo carmine significantly improved visibility of early gastric cancer compared with WLI in all color vision types (P < 0.0001). Although visibility scores under WLI were significantly higher in Type C compared with Types P and D for all objects/lesions, intergroup differences appeared smaller under IEE due to improved visibility in Types P and D.IEE improves visibility of objects/lesions where color information plays a role in detection, regardless of CVD.
Keywords: Endoscopy Upper GI Tract; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE); Endoscopy Lower GI Tract; Quality and logistical aspects; Quality management